Estimating the Size of External Effects of Energy Subsidies - Simon Commander; Zlatko Nikoloski; Maria Vagliasindi (Institute for the Study of Labor (IZA), 2015)
It is widely accepted that the costs of under-pricing energy are large, whether in advanced or developing countries. This paper explores how large these costs can be by focussing on the size of the external effects that energy subsidies in particular generate in two important sectors transport and agriculture in two MENA countries, Egypt (transport) and Yemen (agriculture). Our focus is mainly on the costs associated with congestion and pollution as well the impact of under-priced energy for depletion of scarce water resources including through crop selection. Quantifying the size of external effects in developing countries has received relatively little analytical attention, although there is a significant body of literature for the advanced world. By building on earlier research, as well as employing the UN ForFITS model we are able to provide indicative estimates of the external costs of energy subsidies, as manifested in congestion and pollution. Our estimates using simulations indicate that these costs could be materially reduced by elimination or reduction of energy subsidies. We are also able to describe the impact of energy subsidies on water consumption in a region where water resources are particularly limited. As such, our findings provide further evidence of the adverse and significant consequences of subsidising energy.
Keywords: O13; R41; Q41; Q53; I15; 330; energy subsidies; pollution; congestion; health effects of energy subsidies